2020
DOI: 10.1111/1759-7714.13450
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR enhances breast cancer radioresistance through facilitating HSPA1A expression via sequestering miR‐449b‐5p

Abstract: BackgroundBreast cancer (BRCA) is the leading cause of cancer‐related death in women worldwide. Pre‐ and postoperative radiotherapy play a pivotal role in BRCA treatment but its efficacy remains limited and plagued by the emergence of radiation resistance, which aggravates patient prognosis. The long noncoding RNA (lncRNA)‐implicated mechanisms underlying radiation resistance are rarely reported. The aim of this study was to determine whether lncRNA HOX transcript antisense RNA (HOTAIR) modulated the radiosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 71 publications
1
41
0
Order By: Relevance
“…HOTAIR facilitates expression of the HSPA1A by sequestering miR-449b-5P, its direct suppressor. The HOTAIR/miR-449b-5p/HSPA1A axis represents a new mechanism associated in vitro and in vivo with BC radioresistance [ 147 ].…”
Section: Hotair and Micrornas Interaction In Cancermentioning
confidence: 99%
“…HOTAIR facilitates expression of the HSPA1A by sequestering miR-449b-5P, its direct suppressor. The HOTAIR/miR-449b-5p/HSPA1A axis represents a new mechanism associated in vitro and in vivo with BC radioresistance [ 147 ].…”
Section: Hotair and Micrornas Interaction In Cancermentioning
confidence: 99%
“…In many studies, the intracellular HSP70 level in cancer cells was found to be correlated with their radioresistance [ 195 , 196 , 197 , 198 , 199 , 200 ]. The radioprotective function of inducible HSP70 was also revealed in cancer cells treated with HSP90 activity inhibitors [ 166 , 174 ].…”
Section: Hsf1-mediated Heat Stress Response and Heat Shock Proteinmentioning
confidence: 99%
“…In breast cancer models, the lncRNA HOTAIR has been shown to increase radioresistance through targeting of miR-218 and miR-449b-5p. 42,43 Hu et al showed that HOTAIR is upregulated in breast cancer cell lines over normal tissue and increases in expression after 8 Gy irradiation. Furthermore, they reported that knockdown of HOTAIR prevents sponging of miR-218, which sensitizes cells.…”
Section: Ncrnas In Radiation Responsementioning
confidence: 99%
“…42 Zhang et al reported that HOTAIR sponges miR-449b-5p, which facilitates downstream chaperone protein HSPA1A expression and thereby enhances radioresistance. 43 This provides a potential therapeutic target for the treatment of breast cancer.…”
Section: Ncrnas In Radiation Responsementioning
confidence: 99%
See 1 more Smart Citation